Identification and functional analysis of CORIN variants in hypertensive patients. Issue 12 (26th September 2017) - Zhang, Yue; Zhou, Tiantian; Niu, Yayan; He, Meiling; Wang, Can; Liu, Meng; Yang, Junhua; Zhang, Yonghong; Zhou, Jianping; Fukuda, Koichi; Qin, Jun; Dong, Ningzheng; et al.
Abstract: Corin is a serine protease that activates atrial natriuretic peptide (ANP). CORIN gene variants have been reported in patients with hypertension. To date, however, the prevalence of CORIN variants in hypertensive patients remains unknown. To understand the prevalence and functional significance of CORIN variants in hypertension, we sequenced CORIN exons in 300 normal and 401 hypertensive individuals in a Chinese population and identified nine nonsynonymous variants, of which eight were not characterized previously. Among them, variants c.131A > G (p.Tyr13Cys), c.376G > T (p.Asp95Tyr), c.1094T > G (p.Leu334Trp), and c.1667G > A (p.Arg525His) occurred similarly in both normal and hypertensive individuals. Variants c1139G > A (p.Arg349His), c.2689C > T (p.Pro866Ser), and c.2864C > T (p.Thr924Met) were found once each in hypertensive individuals. Variant c.1683G > T (p.Arg530Ser) occurred preferentially in hypertensive individuals [10/401 (2.5%) vs. 1/300 (0.3%) in normal individuals; P  = 0.023], which was confirmed in another independent cohort [9/368 (2.44%) in hypertensive and 2/377 (0.53%) in normal individuals; P  = 0.033]. In biochemical and cell‐based functional studies, variants p.Arg530Ser and p.Thr924Met, but not p.Tyr13Cys, p.Asp95Tyr, p.Leu334Trp, p.Arg349His, p.Arg525His, and p.Pro866Ser, exhibited reduced pro‐ANP processing activity, which was caused by endoplasmic reticulum retention and poor zymogen activation, respectively. These results indicate that genetic variants impairing corin function are not uncommon in general populations and that such variants may be an important contributing factor in hypertension. Abstract : Corin is a transmembrane serine protease that activates atrial natriuretic peptide (ANP) and regulates blood pressure. In this study, nine nonsynonymous CORIN variants were identified in hypertensive patients in a Chinese population, among which p.Arg530Ser is in the frizzled 2 domain and p.Thr924Met is in the protease domain. Functional studies indicate that p.Arg530Ser and p.Thr924Met causereticulum retention and poor zymogen activation, respectively, thereby impairing the ANP activating activity of corin.